An Alliance of Carbapenem-Resistant Klebsiella pneumoniae with Precise Capsular Serotypes and Clinical Determinants: A Disquietude in Hospital Setting - Elghar Soltani; Alka Hasani; Mohammad Ahangarzadeh Rezaee; Maryam Zaare Nahandi; Akbar Hasani; Pourya Gholizadeh (Canadian Journal of Infectious Diseases and Medical Microbiology)
Carbapenemase-resistant Klebsiella pneumoniae (CRKP) is a genuine burden for physicians and researchers. We aimed at carbapenemase resistance and its relation with capsular serotyping in K. pneumoniae and studied some clinical determinants, which may influence the clinical infections. Initially, 61 K. pneumoniae isolates obtained from various clinical specimens were confirmed at the molecular level and then antimicrobial susceptibility test was performed followed by capsular serotyping performed by multiplex PCR. All isolates were subjected to the detection of carbapenemase genes including blaKPC, blaNDM-1, blaOXA-48, blaVIM, and blaIMP. Clinical and demographic data of all patients were reviewed including age, gender, underlying diseases, and the treatment obtained. Multidrug-resistance was a predominant feature in 77% K. pneumoniae strains. Presence of extended-spectrum beta-lactamase was detected phenotypically in 59% K. pneumoniae strains. Carbapenem resistance was noticed phenotypically in 24.6% isolates. blaOXA-48 and blaNDM-1 were the most frequent carbapenemase genes. blaNDM-1 positive isolates correlated with gentamicin, amikacin, imipenem, and meropenem resistance (p<0.05). The nosocomial isolates mostly harbored blaOXA-48 gene (p<0.02). Amongst all the K. pneumoniae isolates, 59% isolates could be typed and serotype K54 had the highest prevalence followed by K20 and K5. Correlation between the carbapenemase genes, serotype and type of infection showed that blaOXA-48 positive strains had a significant association with K20 serotype and urinary tract infections (p=0.2) while, K20 serotype and blaKPC positive strains were significantly associated with wound infections (K20, p=0.3 and blaKPC, and p=0.4). Mucoid phenotype was not found related to presence of specific carbapenemase genes or serotypes except serotype K20 (p<0.001). Patients with monotherapy had treatment failure in comparison to the combination therapy for blaKPC-associated infections. In conclusion, the present investigation exhibited the significant association between K20 serotype with blaOXA-48. The predominance of K54 reveals the possibility of endemicity in our hospital setting. K. pneumoniae isolated from wound specimens significantly harbors K20 serotype and blaKPC gene. Comprehensive clinical information and the distribution of antibiotic resistance genes, and serotypes may play important roles in the treatment process.